Efektivitas Alat Peraga Mini Solar Panel dengan Model Inkuiri Terbimbing pada Topik Energi Terbarukan untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Sarina; Wiyarsi, Antuni; Pertiwi, Andini; J, Jumadi; Dahliani, Eka (Jurnal Pendidikan Indonesia, 2025)
Critical thinking skills are essential for students to navigate future challenges and comprehend complex issues. However, many students have not been trained to think critically in the context of science, particularly because the learning process still emphasises theoretical learning over active exploration. This study aims to analyse the effectiveness of using mini solar panel teaching aids in conjunction with a guided inquiry model in improving the critical thinking skills of grade VIII junior high school students. This study was a Pre-Experiment with a one-group pretest-posttest Design. The study population consisted of all grade VIII junior high school students, with a sample of class VIII B comprising 31 students. The results showed that mini solar panel teaching aids, combined with a guided inquiry model, were effective in improving students' critical thinking skills, with an average increase in the N-Gain score of 0.63 in the moderate category. Second, there was a significant difference in the average score of students' critical thinking skills before and after the implementation of the teaching aids, with an average pretest score of 5.56 and a post-test score of 11.16. Third, the implementation of mini solar panel teaching aids using a guided inquiry approach had a significant impact on the development of students' critical thinking skills. This study demonstrates that the use of mini solar panel teaching aids in conjunction with a guided inquiry model can be an effective learning method for enhancing students' critical thinking skills in science learning.